Understanding of Accounting Standards in Indonesia - Isthofa, Royan Angga; Faiqoh, Nadia (Proceedings International Conference on Education Innovation and Social Science, 2022)
Accounting standards are an agreement in terms of preparing financial statements. The development of accounting standards in Indonesia continues to increase so that currently there are several kinds of standards for preparing financial statements. The purpose of this study is to understand about Accounting Standards, provide a description of Accounting Standards in Indonesia as well as explain the types of Accounting Standards in Indonesia. The research uses a literature review method in which researchers look for data sources from several university repositories as well as national and international journals. Based on the study conducted, in Indonesia there are 5 types of Accounting Standards in the preparation of financial statements, each of which has its own purpose in its preparation.